2004
DOI: 10.1038/sj.ijir.3901054
|View full text |Cite
|
Sign up to set email alerts
|

Effect of combination endothelial nitric oxide synthase gene therapy and sildenafil on erectile function in diabetic rats

Abstract: Erectile dysfunction associated with diabetes mellitus is caused in part by disordered endothelial smooth muscle relaxation, neuropathy, and a decrease in cavernosal nitric oxide synthase (NOS) activity. The purpose of this study was to determine whether a combination of sildenafil and adenoviral gene transfer of endothelial NOS (eNOS) could enhance the erectile response in diabetic rats. Five groups of animals were utilized: (1) age-matched control rats, (2) streptozotocin (STZ)-induced diabetic rats (60 mg/k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
65
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(70 citation statements)
references
References 44 publications
5
65
0
Order By: Relevance
“…The overall erectile response was greater in diabetic rats receiving eNOS gene therapy and sildenafil than rats receiving sildenafil or eNOS gene alone. [77][78][79] Another in vivo study used adenovirally mediated transfer of eNOS gene with or without cGMP PDE, showing promising results as a future treatment for ED. 80 Myoblast-mediated gene therapy was tested in vivo and was more superior in delivering inducible NOS into the corpus cavernosum than direct adenovirus or a plasmid transfection method.…”
Section: Gene Therapymentioning
confidence: 99%
“…The overall erectile response was greater in diabetic rats receiving eNOS gene therapy and sildenafil than rats receiving sildenafil or eNOS gene alone. [77][78][79] Another in vivo study used adenovirally mediated transfer of eNOS gene with or without cGMP PDE, showing promising results as a future treatment for ED. 80 Myoblast-mediated gene therapy was tested in vivo and was more superior in delivering inducible NOS into the corpus cavernosum than direct adenovirus or a plasmid transfection method.…”
Section: Gene Therapymentioning
confidence: 99%
“…The authors concluded that vitamin E enhanced the therapeutic effect of sildenafil, which indicated a potential means of salvaging erectile function among men who are refractory to sildenafil. 8 Similarly, Bivalacqua et al 12 reported the effect of combination of sildenafil and NO synthase gene therapy on erectile function in STZ diabetic rats. The authors clearly showed that overexpression of eNOS and cGMP in combination with sildenafil significantly increased both the ICP and total ICP to CNS in the STZ diabetic rats, which was similar to the response observed in control rats.…”
Section: Discussionmentioning
confidence: 99%
“…In several cohorts, it has been shown that sildenafil is an effective and well-tolerated treatment for ED in men with diabetes. 7,12,15 However, the results of those studies showed that sildenafil does not have the same efficacy in improving erectile function in diabetic men when compared with other ED etiologies. The decreased efficacy of sildenafil in men with diabetes-related ED lead several authors to investigate several other treatment options such as combination treatments and chronic use of PDE5 inhibitors for the treatment of erectile function in that 'hard to treat' population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the total erectile response in STZ-induced diabetic rats receiving eNOS gene transfer plus sildenafil was greater than STZ-induced diabetic rats receiving eNOS gene transfer or sildenafil alone. 24 …”
mentioning
confidence: 99%